A High-Performance GPU-Accelerated Ray-Tracing Method for Real-Time V2V Channel Modeling - Hu, Shuo; Guo, Li-Xin; Liu, Zhongyu; Zhong, Zhigang; Nan, Zuoyong (IEEE antennas and wireless propagation letters, 2025)
Vehicle-to-vehicle (V2V) communications require highly accurate and real-time channel modeling techniques. The dynamic nature of V2V scenarios demands continuous scene updates while ray-tracing (RT) algorithms typically require substantial computational time to achieve accurate predictions. This letter proposes an OptiX-based graphics processing unit-parallel dynamic shooting and bouncing RT (DSRT) method that combines the advantages of shooting and bouncing ray and RT approaches. The method employs an improved adaptive ray-tube splitting mechanism to improve accuracy. A level of detail based dynamic scene update method further optimizes performance, while OptiX and compute unified device architecture (CUDA) acceleration enable efficient RT. Channel measurements in urban environments demonstrate the high accuracy of our algorithm. Performance evaluation results show that DSRT achieves a parallelization degree exceeding 98.8% and delivers exceptional speedup ratios.